2022
DOI: 10.1029/2021tc006962
|View full text |Cite
|
Sign up to set email alerts
|

From Left Slip to Transpression: Cenozoic Tectonic Evolution of the North Altyn Fault, NW Margin of the Tibetan Plateau

Abstract: The Cenozoic North Altyn Fault (NAF) is a major splay of the Altyn Tagh Fault along the northwestern margin of the Tibetan Plateau, but its role in the development of this plateau margin in response to the India‐Eurasia collision is highly debated. Here, we investigate fault geometry, kinematics, and shortening magnitude along the westernmost 120 km of the NAF. Seismic surveys reveal minimal Cenozoic shortening in the subsurface of the Southeast Tarim Basin and support for large‐scale (>120 km) left slip on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 118 publications
(291 reference statements)
0
10
0
Order By: Relevance
“…Conversely, the eastern Tarim Basin does not display thick Cenozoic sediments, which is more consistent with strike‐slip deformation without significant thrust‐induced loading. Just north of the Altyn Tagh Range is minor subsidence and related sedimentation observed in the gravity and sediment maps (∼3 km) that reflects loading of the Tarim Basin caused by the transpressional deformation observed within this bend in the ATF (e.g., Cowgill et al., 2004; Gao et al., 2022). These observations suggest that the ranges around the western Tarim Basin have experienced more shortening and foreland‐loading throughout the Cenozoic, and thus the present‐day strain patterns have persisted throughout the Cenozoic.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, the eastern Tarim Basin does not display thick Cenozoic sediments, which is more consistent with strike‐slip deformation without significant thrust‐induced loading. Just north of the Altyn Tagh Range is minor subsidence and related sedimentation observed in the gravity and sediment maps (∼3 km) that reflects loading of the Tarim Basin caused by the transpressional deformation observed within this bend in the ATF (e.g., Cowgill et al., 2004; Gao et al., 2022). These observations suggest that the ranges around the western Tarim Basin have experienced more shortening and foreland‐loading throughout the Cenozoic, and thus the present‐day strain patterns have persisted throughout the Cenozoic.…”
Section: Discussionmentioning
confidence: 99%
“…The kinematic model of the North Altyn fault suggests it is a lift‐slip transpressional fault since ca. 17–15 Ma (Cowgill et al., 2000; Gao et al., 2022). Thus, the post‐Miocene vertical and strike‐slip rates of the North Altyn fault are ∼0.13 mm/a and ∼1.67 mm/a, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Based on field observations and seismic data, Gao et al. (2022) determined that ∼2 km vertical uplift and ∼25 km strike‐slip displacement have been absorbed by the North Altyn fault. The kinematic model of the North Altyn fault suggests it is a lift‐slip transpressional fault since ca.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wang et al, 2005;Yin et al, 2002;Yue & Liou, 1999;Yue et al, 2010;Zhou & Graham, 1996). Based on the apatite fission track data obtained from the Altyn Tagh Range and its neighbouring basins, recent studies suggested the primary strike-slip motion occurred along the North Altyn Fault instead of the ATF during the Paleogene (Gao et al, 2022;Wu et al, 2019). However, there is little research on the Mesozoic, espe-…”
Section: Introductionmentioning
confidence: 99%